2012
DOI: 10.1002/ejic.201200622
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Electronic Properties of N‐Heterocyclic Carbene Ligands in the Context of Homogeneous Catalysis and Bioorganometallic Chemistry

Abstract: N‐heterocyclic carbenes (NHCs) have been dominating the world of homogeneous catalysis in an unprecedented manner in the last two decades. Understanding the underlying reasons behind catalysis with NHC ligands has thus become of significant interest. Subscribing to this view, we strive to identify the key attributes of N‐heterocyclic carbene ligands through a combination of experimental and computational studies. Rational catalyst design, by appropriate functionalization of N‐heterocyclic carbene ligands to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 239 publications
(128 reference statements)
0
37
0
Order By: Relevance
“…Hence, achieving base-free Michael addition is of considerable interest and for which the use of bifunctional catalysts containing both an acidic site at the metal center and a basic site in the chelated side arm of the ligand become relevant. This particular concept was developed by us for the nickel N-heterocyclic carbene complexes [263]. …”
Section: Michael Addition Under Base-free Conditionsmentioning
confidence: 99%
“…Hence, achieving base-free Michael addition is of considerable interest and for which the use of bifunctional catalysts containing both an acidic site at the metal center and a basic site in the chelated side arm of the ligand become relevant. This particular concept was developed by us for the nickel N-heterocyclic carbene complexes [263]. …”
Section: Michael Addition Under Base-free Conditionsmentioning
confidence: 99%
“…An interesting point of our inves--tigation, arose from the cyclic voltammetric studies of our complexes, which demonstrated that the presence of external π--stacking additives showed important modifica--tions of the electronic properties of the ligands, as a con--sequence of the strong π--stacking interaction between pyrene and the extended polyaromatic system attached to the NHCs. 6a The effects of modifying the electronic prop--erties of NHCs ligands are known to afford important implications in the context of homogeneous catalysis and bioorganometallic chemistry, 9 and some elegant examples of fine electronic tuning of NHC ligands via remote chem--ical induction have shown to produce relevant effects in catalysis. 10 Benzo--fused nitrogen heterocycles continue to com--mand a great deal of attention because a large number of natural products and pharmaceutical compounds incor--porate these heterocyclic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of palladium nanoparticles in the reaction mixture was confirmed by dynamic light scattering and transmission electron microscopy studies and a mercury poisoning experiment. The complexes C5, bearing benzimidazole and pyridine groups have been proved to be a highly efficient catalyst for the coupling reaction of aryl halides with various substituted acrylates under mild conditions in excellent yields (Table 1, entries [16][17][18][19][20][21][22]. 43 Electron-deficient aryl bromides gave a slightly higher yield than electron-rich ones under the optimized conditions.…”
Section: 38mentioning
confidence: 99%
“…Suzuki coupling reactions carried out using immobilized Pd-NHC catalysts. The palladium catalyst C85 based on modified halloysite nanotubes displayed good activity, allowing the synthesis of several biphenyl compounds in high yield working with only 0.1 mol% palladium loading (Table 12, entries [14][15][16][17][18][19] Applications of a polymer supported air-stable palladium NHC complex with a spacer (catalyst C90,…”
mentioning
confidence: 99%